O Projeto Trilhas: novos olhares e recomendações para a proposta formativa on-line - Slemenson, Maria Mulé (2016)
The aim of this research was to conduct an analysis of the perceptions and recommendations given by literacy professors towards the online learning proposed by Projeto Trilhas. Created in 2012 by Instituto Natura and Comunidade Educativa CEDAC, in partnership with Brazilian Education Ministry (Ministério da Educação MEC), the proposed online learning has educational content designed to support professors who teaches children from 4 to 6 years of age for reading, writing and speaking skills. By encouraging educators to reflect on the conceptions and teaching methods of the Projeto Trilhas, the online programme – the focus of this research – aims to complement the existing education content and to enrich the classroom exercises. As a theoretical basis for this study, it was adopted the reference of writing and reading teachings by Delia Lerner, Claudia Molinari, Mirta Castedo and Ana Teberosky among others. Given the significant scope of Projeto Trilhas and its representative potential amongst different regions and workplaces, the data collection was carried out using the “Survey” methodology. With the help of a structured questionnaire, it was possible to gather responses from 42% of the total population of teachers who completed the online programme, a total of 997 participants, covering different segments: Kindergarten, Primary and Secondary Education. Alongside the user survey, two other phases of work were performed. The first one included the elaboration of a list of possible proficiency and teaching skills that can be developed by educators that adopt Projeto Trilhas methods. In the second phase, the potential development of such proficiency and skills in the online programme activities was verified. Results indicate that, from the educators' perspective, the online programme is a powerful educational strategy that contributes to their training and favours the teaching recommendations to be applied in the classroom. One of the most popular suggestions from the educators was the development of new remote online learning courses, with more study hours, certified by the MEC and addressing other areas of learning. It therefore follows that the objectives that have been established were achieved thanks to the legitimacy of the online programme confirmed by the professors who underwent the online training in Projeto Trilhas, and bolstered by a set of recommendations for the improvement and expansion of the online learning programme